28.3k views
3 votes
(4x + 9)/2 1/3= 3x/0.5

User Gelina
by
4.9k points

1 Answer

5 votes

Answer:

X = 0.9

Explanation:

step-by-step.

4x+9

2

1

3

=

3x

0.5

Step 1: Simplify both sides of the equation.

12

7

x+

27

7

=6x

Step 2: Subtract 6x from both sides.

12

7

x+

27

7

−6x=6x−6x

−4.285714x+

27

7

=0

Step 3: Subtract 27/7 from both sides.

−4.285714x+

27

7

27

7

=0−

27

7

−4.285714x=

−27

7

Step 4: Divide both sides by -4.285714.

−4.285714x

−4.285714

=

−27

7

−4.285714

x=0.9

User Pllumb
by
4.8k points